The Relevance of Character Education in Modern Islamic Education - Ahmad Afendi; Sayed; Nofarita Asyiah (Yayasan Zia Salsabila, 2025)
Character education is an important part of Islamic education that greatly affects how individuals develop their morals and spiritual values. This research investigates how character education is carried out within Islamic education, using a qualitative approach based on a review of existing literature. The qualitative method was selected to explore both the ideas and real-world applications of character education in Islamic education, with a detailed examination of various related sources. The discussion covers important topics like moral values in Islam, ways to teach these values effectively, and the difficulties faced when including character education in the Islamic education curriculum. The results offer valuable information on how character education can be successfully used in Islamic education and what impact it can have on shaping the character and morals of people in society.